Effect Of Preterm Infant Oral Motor Intervention (Piomi) On Feeding Readiness and Feeding Behaviour in Preterm Neonates- A Randomised Control Trial - Shah, Vidhi; Vadiraj Chanageri, Shradha; Patil, Trupti; Sukey, Bhargavi; Padhi, Sunita Brahmanand (Journal of Neonatal Surgery, 2025)
ABSTRACT Objectives: The study aimed to evaluate Preterm Infant Oral Motor Intervention on Feeding Readiness and Feeding Behaviour in Preterm Neonates. Methodology: 32 children diagnosed with Feeding difficulty, divided into two groups: Group A (n = 16, mean age – 30 ±1.25 weeks) which received Preterm Infant Oral Motor Intervention for thrice/day and Group B (n = 16, mean age – 30 ±1.50) which received Oral Motor Stimulation once/day. Both groups underwent sessions over 10 consecutive days. Preterm oral feeding readiness assessment scale, Preterm Infant Breastfeeding Behavior Scale and Weight was taken before and after the intervention. Results: Both groups showed statistically significant improvements across all outcome measures (p<0.002). However, Intervention Group i.e Group A demonstrated a slightly greater improvement in Feeding readiness and Behaviour, weight gain and reduced no. of days to transition from gavage to Oral Feeding. Conclusion: Preterm Infant Oral Motor Intervention and Oral Motor Stimulation both significantly improved feeding readiness, feeding behavior, weight gain, and the transition from gavage to oral feeding in preterm neonates. However, Group A, which received PIOMI, for more no. of times/day, showed greater improvements across all outcome measures. This suggests that increased frequency of specific oral motor intervention for preterm neonates i.e PIOMI may be more effective in enhancing feeding outcomes in preterm infants